To the question of terminology on road transport - Sergei Sergeevich Voitenkov; Dmitriy Vladimirovich Shapoval; Evgeniy Evgenievich Vitvitskiy (Вестник СибАДИ)
This article contains an overview of developing concepts in the road transport industry, such as road transport, transport system and infrastructure; there are definitions of concepts, taken from various sources, including legal documents; there are presented differences in the interpretation of certain concepts. The author makes a conclusion on the terminology development and differences in the interpretation of road transport and its components.